1997
DOI: 10.1080/10402009708983687
|View full text |Cite
|
Sign up to set email alerts
|

Friction, Wear, and Triboelectron Emission of Hydrogenated Amorphous Carbon Films

Abstract: Amwphow and hydrogenated amolphous carbon films were prepared on a g h s substrate using DC magnetron sputtering deposition in gas mixtures of H2 and Ar having different H2 content. T n b~ emission and fiction were measured in a fictional system by sliding an AeOs ball across carbon films in a dry air atmosphere. Wear behavior of the carbon films was investigated by observing t h worn sufaces with a scanning electron microscope (EM) and an atomic force microscope (AFM). Carbon films prepared with low level H2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In a disk drive, electric potentials of up to 0.1 V can be developed between the slider and the disk surface [13,19], indicating that some charge transport has occurred. As examples, Nakayama et al observed triboelectromagnetic phenomena at two kinds of sliding solid-solid interfaces: Al 2 O 3 /a-CH x [20] and diamond/a-CH x [14]. Triboelectromagnetic phenomena were also observed when the a-CH x film was coated with PFPE fluid [8,11,16].…”
Section: Introductionmentioning
confidence: 90%
“…In a disk drive, electric potentials of up to 0.1 V can be developed between the slider and the disk surface [13,19], indicating that some charge transport has occurred. As examples, Nakayama et al observed triboelectromagnetic phenomena at two kinds of sliding solid-solid interfaces: Al 2 O 3 /a-CH x [20] and diamond/a-CH x [14]. Triboelectromagnetic phenomena were also observed when the a-CH x film was coated with PFPE fluid [8,11,16].…”
Section: Introductionmentioning
confidence: 90%
“…on the macroscale level) have been studied in papers [24,331]. The corresponding yield of charged particles and photons has been measured during scratching of different solids with a diamond stylus at sliding velocities of 2 to 7 cm/s, tip radius 10 mm and loading force 0.5 N in the ambient atmosphere.…”
Section: Phenomena Of Particle and Acoustic Emissionmentioning
confidence: 99%
“…Another factor is due to the triboelectromagnetism [23,24,331], leading to a decomposition of the lubricating oil molecules when sliding. Due to this reason the so-called ªproximity recordingº disk sliders have been implemented successfully in the magnetic recording industry during the last few years [332].…”
Section: Some Industrial Aspectsmentioning
confidence: 99%
“…The test apparatus used here differs significantly from those used in previous studies that measured the triboemission from hydrogenated carbon films in the vicinity of a sliding contact [26][27][28][29][30]. The spatial resolution achieved with this technique allows the emission to be visualised, defining its shape and size.…”
Section: Triboemission Measurementsmentioning
confidence: 88%